Enhancement of Plant Monitoring Using IoT - Pravin, A; Prem Jacob, T; Asha, P (International Journal of Engineering and Technology, 2018)
Agriculture is the backbone of our country; most of the people depend on agriculture. The main issue in agriculture is water scarcity. The water resource is not used in an effective manner, so the water is wasted. In order to overcome this irrigation process can be automated. The use of Internet of things in this field will be helpful to reduce the wastage of water. So that the temprature as well as humidity and light are measured by means of sensors and depend up on the outcome further processing can be performed. We propose a system that will capture all the details about the soil and the temprature by means of different sensors. The sensed information will be send to the processor and depends up on the outcome the alert message will be passed and the appropriate amount of water will be released to the crop. And the further information related to the fertilizer quantity and whether there is any set of serious attack on the crop that will also be identified by the system. The advantage of this system will be finding the current issues in terms of soil condition, humidity and crop condition and the information will be immediately passed to the farmers.Â Â